2008
DOI: 10.1007/s00296-008-0766-6
|View full text |Cite
|
Sign up to set email alerts
|

Association of macroscopic gut inflammation with disease activity, functional status and quality of life in ankylosing spondylitis

Abstract: The aim of this cross-sectional study was to evaluate the frequency of intestinal inflammation and its association with disease activity, functional status and quality of life in patients with ankylosing spondylitis (AS). A total of 25 patients with AS had undergone ileocolonoscopy and concomitant histological study. Clinical and demographical parameters, BASDAI, BASFI, and SF-36 scores were compared between patients with and without macroscopic gut inflammation (MGI). Colonoscopic study revealed MGI in 9 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 14 publications
0
7
0
2
Order By: Relevance
“…These findings are contrary to those of a previous study that showed serum levels of acute phase reactants to be similar in patients with AS, regardless of gut inflammation. However, in their study, higher bath AS disease activity index scores were found in patients with gut inflammation than in those without gut inflammation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…These findings are contrary to those of a previous study that showed serum levels of acute phase reactants to be similar in patients with AS, regardless of gut inflammation. However, in their study, higher bath AS disease activity index scores were found in patients with gut inflammation than in those without gut inflammation [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are also HLA diVerences: AS is associated with the class I HLA-B27 and RA with the class II HLA-DR4. It is also likely that at least a mild degree of inXammation of the bowel may be evident in those with AS [31], while this is generally considered absent in RA. Additionally, the mechanisms of joint damage also diVer, with the synovium being critical in RA as opposed to bone in AS [32].…”
Section: Inxammatory Arthritis and Disturbed T Cell Functionmentioning
confidence: 93%
“…It is well documented that there is a strong link between gut inflammation [46] and/or AS [47, 48]. The level of total [49] and secretory IgA immunoglobulins [50] increased in the majority of patients with AS.…”
Section: Evidence Of Subclinical Microbial Infections In As and CDmentioning
confidence: 99%